A review of the agriculture literature in Malaysian and Indonesian accounting journals - Mustafa, Hasri; Lestari, Retno Martanti Endah (Penerbit UTHM, 2021)
This article discusses the scope related to Malaysian and Indonesian accounting research in agricultural literature. This discussion was based on two well-known Malaysian accounting journals and many were referred from 2008 to 2016, recognized as Accounting Overview Malaysia (MAR) and Asian Business and Accounting Journal (AJBA), and three Indonesian accounting journals namely Economic & Financial Studies (SEZ) , Gadjah Mada International Business Journal (GamaIJB) and Indonesian Accounting and Finance Journal (JAKI). In MAR and AJBA, Corporate Governance, Auditing, Financial Accounting Reporting, and Management Accounting are the most widely published topics. In SEZ, Economy, Finance, Public Sector Accounting and Taxation; GamaIJ, Management / Managerial Accounting and Finance; and JAKI, Management / Managerial Accounting, Financial Accounting, and Reporting Audit are the most widely published topics. This article proposes peculiarities, non-company and non-professional attributes as opportunity-researched variable fields for future agricultural studies. This article concludes with a reminder of the direction that leads to Malaysian and Indonesian accounting research, including the ontological difference between agricultural studies and accounting minutes while the latter seeks to fulfill generalizations, company attributes and stereotyped-research-variable professionals. It was concluded there is no difference in the average number of journals published in Malaysia and Indonesia with the test.